Corona Virus – Dentist’s Perspective - K.M.K. Masthan1, E.P. Sridevi Anjuga2, N.Aravindha Babu3 , E.Rajesh4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A novel coronavirus (COVID-19) contributes to human-to - human transmission. The COVID-19 has beenrecently identified in infected patient’s saliva. Transmission of COVID-19 via contact with droplets andaerosols generated during clinical dental procedures is predicted. There is a need to start up investigationsinto the identification of COVID-19 in oral fluids and its effects on the transmission of this virus, which isnecessary for improving successful preventive strategies, in health care professionals particular for dentistswho perform aerosol-generating procedures.In addition to the standard precautions, some special precautionsthat should be implemented during an outbreak have been raised in this review.